2008
DOI: 10.1364/oe.16.019097
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of optical pulse coding in spontaneous Brillouin-based distributed temperature sensors

Abstract: Abstract:A theoretical and experimental analysis of optical pulse coding techniques applied to distributed optical fiber temperature sensors based on spontaneous Brillouin scattering using the Landau-Placzek ratio (LPR) scheme is presented, quantifying in particular the impact of Simplex coding on stimulated Brillouin and Raman power thresholds. The signal-to-noise ratio (SNR) enhancement and temperature resolution improvement provided by coding are also characterized. Experimental results confirm that, differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
65
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 19 publications
1
65
1
Order By: Relevance
“…We show that with such multimode lasers we can increase the maximum input power threshold value before the onset of fibre nonlinearities, enhancing the sensor performance. In addition, this technique can be efficiently combined with the use of optical pulse coding techniques for further performance enhancement [3].In SpBS-based sensors the SpBS intensity (DP B ) and BFS (Dv B ) are both linearly dependent on strain and temperature; this makes the simultaneous strain (D1) and temperature (DT ) sensing along a single optical fibre possible by using the following matrix relation: …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We show that with such multimode lasers we can increase the maximum input power threshold value before the onset of fibre nonlinearities, enhancing the sensor performance. In addition, this technique can be efficiently combined with the use of optical pulse coding techniques for further performance enhancement [3].In SpBS-based sensors the SpBS intensity (DP B ) and BFS (Dv B ) are both linearly dependent on strain and temperature; this makes the simultaneous strain (D1) and temperature (DT ) sensing along a single optical fibre possible by using the following matrix relation: …”
mentioning
confidence: 99%
“…We show that with such multimode lasers we can increase the maximum input power threshold value before the onset of fibre nonlinearities, enhancing the sensor performance. In addition, this technique can be efficiently combined with the use of optical pulse coding techniques for further performance enhancement [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it has been recently demonstrated that optical pulse coding techniques provide enhanced SNR in both SpBS-based [7] and SpRS-based [5] sensors, allowing for significantly improved sensing performance. However, the use of coding is limited in SpBS-based sensors by the SBS threshold, which constrains the maximum optical power at the fiber input [7].…”
Section: Theorymentioning
confidence: 99%
“…Finally, it has been recently demonstrated that optical pulse coding techniques provide enhanced SNR in both SpBS-based [7] and SpRS-based [5] sensors, allowing for significantly improved sensing performance. However, the use of coding is limited in SpBS-based sensors by the SBS threshold, which constrains the maximum optical power at the fiber input [7]. In the proposed scheme employing FP lasers this limitation can be effectively overcome; the total laser power is in fact distributed among several longitudinal modes, each one being limited by the SBS threshold, thus allowing for higher total peak power levels.…”
Section: Theorymentioning
confidence: 99%